(untitled) (Global Journal of Science Frontier Research, 2020)
The aim of this study was to carry microbiological assessment of the prevalence of Staphylococcus aureus and Escherichia coli associated sliced ready-to-eat water melon and pineapple fruits. A total of 10 sliced pineapple and water melon fruits were purchased from different vendors at Akpan Andem Market, Uyo. The fruit samples were aseptically transported to the laboratory and processed using standard techniques. Enumeration of total heterotrophic bacteria and fungi, and isolation, characterization and identification of Staphylococcus aureus and Escherichia coli were all done using standard microbiological techniques. Antibiotic sensitivity test was carried out using the Kirby Bauer disk diffusion test. The results of the aerobic bacterial and fungal counts indicated that the highest bacterial count was 1.85 x 10 4 for water melon and 1.80 x 10 4 cfu/g for pineapple while those of the fungi were 1.3 and 1.4 x 10 3 cfu/g, respectively. For E. coli, the least and highest zones of inhibitions were 6.00±1.05 and 23.37±1.20 mm for isolates WS5 and PA3, respectively against CEP and CPX which were Ciprofloxacin and Ceporex. A total of 4 out of 10 isolates showed multi-drug resistance (resistance to at least 2 antibiotics) and these were isolates PA4, PA1, WS4, and WS5.